Interplay between singing and cortical processing of music: a longitudinal study in children with cochlear implants - Torppa, Ritva; Huotilainen, Minna; Leminen, Miika; Lipsanen, Jari; Tervaniemi, Mari (Frontiers in Psychology, 2014)
Informal music activities such as singing may lead to augmented auditory perception and attention. In order to study the accuracy and development of music-related sound change detection in children with cochlear implants (CIs) and normal hearing (NH) aged 4-13 years, we recorded their auditory event-related potentials twice (at T1 and T2, 14-17 months apart). We compared their MMN (preattentive discrimination) and P3a (attention towards salient sounds) to changes in piano tone pitch, timbre, duration, and gaps. Of particular interest was to determine whether singing can facilitate auditory perception and attention of CI children. It was found that, compared to the NH group, the CI group had smaller and later timbre P3a and later pitch P3a, implying degraded discrimination and attention shift. Duration MMN became larger from T1 to T2 only in the NH group. Duration MMN became larger from T1 to T2 only in the NH group. The development of response patterns for duration and gap changes were not similar in the CI and NH groups. Importantly, CI singers had enhanced or rapidly developing P3a or P3a-like responses over all change types. In contrast, CI non-singers had rapidly enlarging pitch MMN without enlargement of P3a, and their timbre P3a became smaller and later over time. These novel results show interplay between MMN, P3a, brain development, cochlear implantation and singing. They imply an augmented development of neural networks for attention and more accurate neural discrimination associated with singing. In future studies, differential development of P3a between CI and NH children should be taken into account in comparisons of these groups. Moreover, further studies are needed to assess whether singing enhances auditory perception and attention of children with CIs.